A destination imagery processing model: Structural differences between dream and favourite destinations. (January 2019) - Cardoso, Lucília; Dias, Francisco; de Araújo, Arthur Filipe; Andrés Marques, Maria Isabel
Highlights: Destination imagery is mostly built on holistic elements. Favourite and dream destinations' imagery are structurally different. Imagery processing differs according to tourists' country of origin. Favourite destinations' imagery is connected to the retrospective memory. Dream destinations' imagery is built on prospective memory. Abstract: The present paper aims at understanding how destination imagery is processed in tourists' working memory. The research focuses on two highly desirable, but contrasting, destination brand categories: Favourite Destination, which involves retrospective memory of positive experiences in situ ; and Dream Destination, based on tourists' prospective memory. Through an online multilingual survey, 23, 446 responses consisting of perceptions, evoked by way of free-recall, associated to Dream and Favourite Destinations, were collected. Findings point to clear structural differences between the imagery of Dream and Favourite Destinations. Additionally, a theoretical destination imagery model that offers a basis for future studies is proposed, and some managerial implications of significant relevance to destination marketing are discussed.